2021
DOI: 10.3389/fonc.2021.693353
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes Related to CD8+ T-Cell Infiltration as Prognostic Biomarkers for Lung Adenocarcinoma

Abstract: BackgroundCD8+ T cells are one of the central effector cells in the immune microenvironment. CD8+ T cells play a vital role in the development and progression of lung adenocarcinoma (LUAD). This study aimed to explore the key genes related to CD8+ T-cell infiltration in LUAD and to develop a novel prognosis model based on these genes.MethodsWith the use of the LUAD dataset from The Cancer Genome Atlas (TCGA), the differentially expressed genes (DEGs) were analyzed, and a co-expression network was constructed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
0
6
1
Order By: Relevance
“…These results were con rmed again in our study, and we also found that in addition to B cells and T cells, MFNG was also closely related to many other immune cells, indicating that MFNG might lead to tumorigenesis by regulating the immune microenvironment in the body. Du et al found that ALG3 was associated with CD8 + T cell in ltration and closely related to the prognosis of LUAD [32] , while we found that ALG3 had a higher correlation with Tcm and mast cells. Tcm [33] and Mast cells [34] have been proved to be closely related to tumorigenesis, which suggests that ALG3 may participate in tumor progression by regulating these immune cells, which needs further study.…”
Section: Discussioncontrasting
confidence: 45%
“…These results were con rmed again in our study, and we also found that in addition to B cells and T cells, MFNG was also closely related to many other immune cells, indicating that MFNG might lead to tumorigenesis by regulating the immune microenvironment in the body. Du et al found that ALG3 was associated with CD8 + T cell in ltration and closely related to the prognosis of LUAD [32] , while we found that ALG3 had a higher correlation with Tcm and mast cells. Tcm [33] and Mast cells [34] have been proved to be closely related to tumorigenesis, which suggests that ALG3 may participate in tumor progression by regulating these immune cells, which needs further study.…”
Section: Discussioncontrasting
confidence: 45%
“…Tian et al showed that the high infiltration of M0 macrophages and resting CD4 memory T cells are associated with an unfavorable prognosis in glioma. 30 Conversely, previous studies have suggested that the infiltration of the CD8 T cells was positively correlated to improve prognosis and survival in several cancers, including melanoma, 31 lung adenocarcinoma, 32 and cutaneous angiosarcoma. 33 In line with these results, this might partly explain that the high‐ ITGA5 group had a poorer prognosis than that of the low‐ ITGA5 group in patients with LSCC.…”
Section: Discussionmentioning
confidence: 99%
“…We rstly revealed that AMDHD1 was highly expressed in LUAD and its overexpression was correlated with patients' poor outcome. GAPDH was found to be one of ve key genes related to prognosis and CD8 + T-cell in ltration in LUAD [22,23]. Moreover, Sakthidhasan et al [24] con rmed the apoptotic and anti-proliferative potential of GAPDH against human lung carcinoma.…”
Section: Discussionmentioning
confidence: 98%